2015
DOI: 10.1039/c4ra11081a
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular proton transfer in cyclic carbonate synthesis from epoxide and carbon dioxide catalyzed by azaphosphatranes: a DFT mechanistic study

Abstract: The activity of azaphosphatranes, novel types of non-metal and solvent-free catalysts for the synthesis of cyclic carbonates from epoxides and CO2, is unraveled by DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…So, the effect of substitution on the aromatic rings of complexes was investigated. 10 The experimental results in Table 4 showed that although this series of catalysts had good catalytic performance under optimal conditions (110 o C, 5 h, 2 MPa), the catalytic activity of these catalysts exhibited some difference for different substitutions. Ko's and present works proved that zinc complexes with phenoxide ligands possessed excellent catalytic performance for the coupling reaction of CO 2 and epoxide.…”
Section: Complexesmentioning
confidence: 95%
See 3 more Smart Citations
“…So, the effect of substitution on the aromatic rings of complexes was investigated. 10 The experimental results in Table 4 showed that although this series of catalysts had good catalytic performance under optimal conditions (110 o C, 5 h, 2 MPa), the catalytic activity of these catalysts exhibited some difference for different substitutions. Ko's and present works proved that zinc complexes with phenoxide ligands possessed excellent catalytic performance for the coupling reaction of CO 2 and epoxide.…”
Section: Complexesmentioning
confidence: 95%
“…The catalyst was applicable to a variety of terminal epoxides to produce the corresponding cyclic carbonates with 10 excellent yields, with the exception of isobutylene oxide (entry 5) and cyclohexene oxide (entry 6), which was probably due to their higher steric hindrance. 66,67 This steric effect was more likely to hinder the nucleophilic attack of the epoxide rather than its coordination to the Lewis acid metal centre.…”
Section: 9mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, appropriate catalysts are required to carry out CO 2 conversion reaction at relatively mild temperature and pressure conditions. Thus, a wide array of catalysts, such as metal oxides, alkali halides, ionic liquids, quaternary ammonium salts, organocatalysts, metal–organic frameworks, and transition metal complexes, [11] has been developed. The transition metal complex catalysts, which exhibit high activity and stability, have been given intensive attention.…”
Section: Introductionmentioning
confidence: 99%